AKIBAT HUKUM TERHADAP PENGHIBAHAN SELURUH HARTA WARISAN OLEH PEWARIS SEHINGGA MELANGGAR LEGITIME PORTIE AHLI WARIS DITINJAU DARI KUHPERDATA (STUDI PUTUSAN NOMOR 188/PDT.G/2013/PN.SMG) - RIVERA WIJAYA (PREMISE LAW JURNAL, 2016)
In any society, a hibah (grant) is not uncommon; it is done by a person as the realization of his freedom to organize his property. However, it is necessary to know that has its own rule which has to be obeyed. A grant which violates legitime portie (legitimate portion) of another legitimaris (heir) will cause revocation. Therefore, it is necessary to study the organization of a grant and a grant by will in the Civil Code, how about the legal consequence of giving a grant which violates legitimate portion of a heir by a testator, and whether judge’s consideration and Ruling No. 188/Pdt.G/2013/PN.Smg on giving a grant of the whole inheritance which violates legitimate portion of a heir are correct. Keywords: Grant, Grant by Will, Legitimate Portion or Legitime Portie